Performance of Kidney Injury Molecule-1 and Liver Fatty Acid-Binding Protein and Combined Biomarkers of AKI after Cardiac Surgery - Parikh, Chirag R. (American Society of Nephrology, 2013)
BACKGROUND AND OBJECTIVES: AKI is common and novel biomarkers may help provide earlier diagnosis and prognosis of AKI in the postoperative period. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This was a prospective, multicenter cohort study involving 1219 adults and 311 children consecutively enrolled at eight academic medical centers. Performance of two urine biomarkers, kidney injury molecule-1 (KIM-1) and liver fatty acid-binding protein (L-FABP), alone or in combination with other injury biomarkers during the perioperative period was evaluated. AKI was defined as doubling of serum creatinine or need for acute dialysis. RESULTS: KIM-1 peaked 2 days after surgery in adults and 1 day after surgery in children, whereas L-FABP peaked within 6 hours after surgery in both age groups. In multivariable analyses, the highest quintile of the first postoperative KIM-1 level was associated with AKI compared with the lowest quintile in adults, whereas the first postoperative L-FABP was not associated with AKI. Both KIM-1 and L-FABP were not significantly associated with AKI in adults or children after adjusting for other kidney injury biomarkers (neutrophil gelatinase-associated lipocalin and IL-18). The highest area under the curves achievable for discrimination for AKI were 0.78 in adults using urine KIM-1 from 6 to 12 hours, urine IL-18 from day 2, and plasma neutrophil gelatinase-associated lipocalin from day 2 and 0.78 in children using urine IL-18 from 0 to 6 hours and urine L-FABP from day 2. CONCLUSIONS: Postoperative elevations of KIM-1 associate with AKI and adverse outcmes in adults but were not independent of other AKI biomarkers. A panel of multiple biomarkers provided moderate discrimination for AKI.